A8.14 CD39 and CD73 transgenic exosomes and recombinant fusion protein as novel therapeutics for the treatment of inflammatory disease. (13th February 2015) - Finn, JD; van Ittersum, J; Broekstra, N; Tak, PP; Vervoordeldonk, MJ
Abstract : Background and objectives: The conversion of extracellular ATP (eATP) to adenosine is an important mechanism of immune suppression through the coordinated activity of two enzymes, CD39 and CD73. CD39 is a membrane bound ATPase, and CD73 is a membrane bound ectonucleotidase that converts AMP to adenosine. We have previously presented evidence that the balance between pro-inflammatory eATP and anti-inflammatory adenosine is skewed in the synovial compartment of rheumatoid arthritis patients. Here we developed strategies for the use of CD39 and CD73 in inflammatory disease, including a soluble Recombinant Anti-Inflammatory fusioN (RAIN) CD39-CD73 fusion protein and transgenic exosomes containing CD39 and CD73. Materials and methods: Whole blood inflammasome activation assay was performed by incubating whole blood with CD39-CD73 samples prior to 2 h LPS stimulation followed by a 1 h ATP stimulation. Pro-inflammatory cytokine/chemokine levels were measured by ELISA. Cell factories seeded with stably expressing 293 cells were used for large scale production of RAIN or CD39-CD73 exosomes. Conditioned serum-free media was collected every 3–5 days until a total of ˜10 L was collected. Conditioned media was concentrated (100 fold) by tangential-flow filtration (TFF) and RAIN was purified by anion-exchange chromatography, whereas exosomes were purified using Total Exosome Isolation reagent. Large scale batches of RAIN and exosomes were characterised by western blot and CD39-CD73 activities were measured by malachite green assay. Results: Small scale batches of CD39-CD73 containing exosomes or RAIN were potent in reducing IL-1β secretion in a whole blood inflammasome activation assay (IL-1β EC50: RAIN ˜4000 pM, exosome ˜100 pM). Large scale production of RAIN was successful and yielded ˜2.5 mgs with ˜90% purity. The protein had a high specific activity (˜16000 U/μg CD39 activity, 24400 U/μg CD73 activity). Exosome purification yielded ˜25 mls of CD39-CD73 containing exosomes with ˜1316, 4000 U/mL (36, 5000 U/μg) CD39 activity and ˜253, 9000 U/mL (13, 5300 U/μg) of CD73 activity. These yields are sufficient for future in vivo studies. Interestingly, the exosomal enzymes had significantly higher specific activity (5–20 fold) when compared with RAIN. Conclusion: These data demonstrate that exosome or fusion protein delivery of CD39 and CD73 is effective in reducing pro-inflammatory cytokine production in vitro, and that large scale production of CD39 and CD73 containing fusion protein or exosomes is feasible.